2014
DOI: 10.1007/s10482-014-0344-8
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenomic and molecular marker based taxonomic framework for the order Xanthomonadales: proposal to transfer the families Algiphilaceae and Solimonadaceae to the order Nevskiales ord. nov. and to create a new family within the order Xanthomonadales, the family Rhodanobacteraceae fam. nov., containing the genus Rhodanobacter and its closest relatives

Abstract: The current taxonomy of the order Xanthomonadales is highly problematic and no comprehensive phylogenomic studies have been completed that include the most divergent members within the order. In this work, we have completed a phylogenomic analysis of a wide range of genomes, five of which were sequenced for the first time for this work, representing the vast majority of the diversity within the order Xanthomonadales. Using comparative genomic techniques, we have identified a large number of conserved signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 55 publications
1
65
0
1
Order By: Relevance
“…oryzicola and X. translucens . Although not otherwise closely related (Naushad et al, 2015), these nominally enter via stomata and propagate throughout the mesophyll parenchyma, causing leaf streak disease, in small grain cereals and forage grasses from a sub-set of the Poaceae /grass plant family, specifically the BEP clade (GPWGII, 2012). However, these plants have highly water-repellent leaves (Neinhuis and Barthlott, 1997), a function of their vertical/upright nature and hydrophobic surface (Koch et al, 2008), which limits bacterial colonization and stomatal access (Beattie, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…oryzicola and X. translucens . Although not otherwise closely related (Naushad et al, 2015), these nominally enter via stomata and propagate throughout the mesophyll parenchyma, causing leaf streak disease, in small grain cereals and forage grasses from a sub-set of the Poaceae /grass plant family, specifically the BEP clade (GPWGII, 2012). However, these plants have highly water-repellent leaves (Neinhuis and Barthlott, 1997), a function of their vertical/upright nature and hydrophobic surface (Koch et al, 2008), which limits bacterial colonization and stomatal access (Beattie, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For two of them, X. albilineans and X. sacchari , genomic analyses demonstrated that they do not contain an Hrp T3SS (Pieretti et al, 2009; Studholme et al, 2011). In contrast, the 48 available genome sequences from seven different pathovars of X. translucens (Wichmann et al, 2013; Gardiner et al, 2014; Pesce et al, 2015a,b; Hersemann et al, 2016, 2017; Jaenicke et al, 2016; Peng et al, 2016) and draft genome sequence of X. hyacinthi (Naushad et al, 2015) revealed that all of them contain an Hrp T3SS the genetic organization of which is at variance to those from the clade-2.…”
Section: Introductionmentioning
confidence: 93%
“…CSIs and CSPs have recently been used to revise the taxonomy of a diverse range of prokaryotic groups at different taxonomic levels (e.g., Cyanobacteria, Halobacteria, Xanthomonadales and Burkholderia) Howard-Azzeh et al 2014;Sawana et al 2014;Naushad et al 2015). In this work we have identified 32 CSIs, nine of which are characteristic of the members of the phylum Chlamydiae.…”
Section: Molecular Markers Distinguishing the Two Main Groups Of Chlamentioning
confidence: 99%